Clinical classification of liver cirrhosis - a way to plan individual definitive treatment - Petiunin, Oleksii; Shevchenko, Rostislav; Brek, Ostap; Kolomensky, Oleksii (My University, 2024)
Aim: To develop clinical classification of liver cirrhosis, which can aid individualization and planning definitive treatment for this group of patients. Materials and Methods: Computerized search of the literature was performed via PubMed using the following medical subject headings or keywords: “liver”, “cirrhosis” and “classification”; or “liver”, “cirrhosis” and “complications”; or “liver”, “cirrhosis” and “treatment”; or “portal” “, “hypertension” and “complications”. Articles were independently evaluated by each author, the etiological, orphological and current clinical classifications of LC were analyzed, their advantages and disadvantages identified, and after discussion classification of LC was developed by consensus. Conclusions: The developed clinical classification of liver cirrhosis will facilitate the planning of therapeutic tactics for each patient, allow to personalize the treatment of patients with this pathology.
Keywords: liver cirrhosis; clinical classification; liver cirrhosis complications; portal hypertension; 2024а